Overview of the antenatal detection of lymphatic malformation, its associated genetic factors, and the complications - Mohd Nor, Nurul Huda; Mohd Nor, Khadijah; Maniam, Sandra; Hod, Rafidah (Universiti Malaya, 2024)
Lymphatic malformation (LM) is a dysfunction of the lymphatic system that is associated with genetic diseases. The clinical manifestation is established, but the outcome concerning genetic abnormalities is still not well understood. This review reports the advancement of technology in detecting LM antenatally, its associated genetic factors, and the complications of LM. Articles which were mainly case reports published from 1983 to 2023 were obtained from the search in Ovid MEDLINE and Scopus using the keywords “gene*”, OR, “DNA”, OR “epigenetic*” AND “lymphatic malformation” OR “cystic hygroma”. The advancement of technology over the years has contributed to the various types of genetic investigations conducted on a foetus with LM, including fluorescence in situ hybridization and multiplex ligation-dependent probe amplification. Poor prognosis indicated by the presence of genetic or karyotype abnormality results in opted termination of pregnancy, intrauterine death, or death at early hours of life. The PTPNII, FOXC2, FOXF1, and SRY genes and various chromosome abnormalities are associated with LM. The complications of LM include bone deformity, cardiac and urinary anomalies, and the worst is foetal hydrops. This critical dysfunction warrants future research directions to identify risk factors or biomarkers to prevent future cases of pregnancy with LM.